(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Recurrent pregnancy loss is common problem now a days and is commonly found in our daily practice.There are so many causes that are established as causative factors for recurrent pregnancy loss. Among them systemic causes includes uncontrolled diebetes mellitus, uncontrolled chronic hypertension, hypothyroidism and local causes includes uterine polyp, uterine fibroid, cervical incompetency etc. Anti-phospholipid syndrome has recently been found to be one of the causes for recurrent pregnancy loss and we have not yet enough study in our country regarding this problem that causes recurrent pregnancy loss. Pregnancy with Anti-phospholipid Syndrome (APS) is rare and it is one of the important factor that causes recurrent pregnancy loss at any trimester of pregnancy. Early diagnosis and pre-conceptional precaution for prevention of recurrent pregnancy loss is essential to deliver a healthy fetus in a diagnosed case of APS. Three cases of anti-phospholipid syndrome (APS) are reported here who have successfully deliverd healthy baby. All the cases were presented with the complaints of recurrent pregnancy loss. Bangladesh J Obstet Gynaecol, 2014; Vol. 29(2) : 106-110